Factors associated with treatment adherence to treatment among in patients with type 2 diabetes in Iran: A cross-sectional study - Pourhabibi, Nasrin; Mohebbi, Bahram; Sadeghi, Roya; Shakibazadeh, Elham; Sanjari, Mojgan; Tol, Azar; Yaseri, Mehdi (Frontiers in Public Health, 2022)
Introduction: Diabetes is a chronic metabolic disorder that affects millions of people worldwide. Adherence to treatment is a key determinant to proper management. This study aimed to assess the predictors of treatment adherence among patients with type 2 diabetes. Materials and Methods: This cross-sectional study was conducted among 704 patients with type 2 diabetes referred to three diabetes clinics in Kerman city. Data were collected using treatment adherence questionnaire and functional communicative critical health literacy (FCCHL). Data were analyzed using descriptive statistics, Pearson Correlation Coefficient and multivariate regression analysis. Significance level was considered less than 0.05. Results: The study results showed that health literacy, HbA1c and income were main predictors of diabetes treatment adherence. The score for adherence increases by 3.64 points for every point increase in health literacy. In addition, an increase in HbA1c decreases the adherence score by 1.84. The treatment adherence score increases by 2.54 for those with sufficient family income and by 0.76 for those with relatively sufficient family income in compare to those with insufficient family income. Conclusion: The results of the present study showed that several factors can influenced diabetes treatment adherence. Planning theory-based interventions to improve the determinants can be helpful in this regard.